Pengaruh Bonus Demografi Terhadap Pertumbuhan Ekonomi di Provinsi Sumatera Barat - Maizul Rahmizal; Mayang Marisa Rahman (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the influence of the dependency ratio, Human Development Index (HDI), and Labor Force Participation Rate (LFPR) on economic growth in West Sumatra Province. Secondary data were obtained from the Central Statistics Agency (BPS) covering 19 districts/cities in 2020–2024. The analysis used multiple linear regression based on panel data with a random effects model as the best model. The results show that the dependency ratio and HDI have a significant positive effect on economic growth, while the LFPR has a positive but insignificant effect. The results of this study identify that demographic structure and improvements in population quality have contributed to economic growth, but the potential workforce has not been fully absorbed. Therefore, policies are needed that can optimize workforce absorption through improving skills, education, and creating jobs that are in line with the economic needs of West Sumatra Province.